Talent management in the process of employee retention in Shared Services Centers - Dąbrowski, Julian (Zarządzanie talentami w procesie utrzymania pracowników w centrum usług wspólnych, 2019)
The aim of the article is to specify how Shared Services Centers (SSC), can use talent management practices to retain employees. For this purpose, theoretical studies including contemporary scientific literature as well as empirical studies covering a survey of 249 respondents who were current employees of Shared Service Centers located in the city of Poznań were carried out. The subjective scope of the study has been narrowed down to minimize the risk of interpretational error resulting potentially from differences in the industry context. The author places talent management in the process of employee retention, and then discusses the results of empirical research. He defines the perception of talent management concept by employees, and also indicates statistically significant differences that may affect the shaping of intra-organizational processes
Management Forum, 2019, vol. 7, no. 1, s. 1-7
Keywords: talent management; shared services center (SSC); employee retention; zarządzanie talentami; centrum usług wspólnych; utrzymanie pracowników